A convenient platform for real‐time non‐contact thermal measurement and processing - Choi, Hyosung; Soeriawidjaja, Banyu Firdaus; Lee, Sang Hak; Kwak, Minseok (Bulletin of the Korean Chemical Society, 2022)
Temperature is one of crucial and integral parts of chemical experiments. Since the properties or shape of the material may change depending on the temperature, the device that measures it plays a vital role in an experiment. Such devices commonly used in experiments to this day are unable to perform temperature measurement and data processing simultaneously. Here, we present a low‐price, non‐contact convenient platform capable of solving both problems at the same time, with automatically set different measurement time intervals for each experiment, and shows processed data anywhere real‐time on the Internet. This device can operate within temperature range of −20 and 80 °C with a respectable error range of ±2.5 °C. An affordable device allows us to simply monitor and immediately display temperature.